1972
DOI: 10.1139/m72-053
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cellulase from Ruminococcus

Abstract: FUSEE, M. C., et J. M. LEATHERWOOD. 1972. Regulation of cellulase from Rln~ri~rococcrrs. Can. J.Microbiol. 18: 347-353. On a examine la regulation de la cellulose chez Rr~lninococcrrs nlbrrs et R. flavefacielu. L'hydrolyse de la cellulose, cornme mesuree par la for~nation des zones claires autour des colonies bacteriennes qui se developpent sur cellulose gelosee en tubes enrobes, est inhibee par des niveaux moyens de cellobiose. U n intermediaire dans le n~etabolisme de la cellobiose peut Ctrc responsable de I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
1

Year Published

1973
1973
2002
2002

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 4 publications
4
17
0
1
Order By: Relevance
“…The greatly enhanced CMcellulase activity in cellobiose-limited continuous cultures suggested that synthesis of this enzyme is catabolite repressed, as previously reported for the cellulase of R. albus (Fusee & Leatherwood, 1972) and a cellulolytic strain of PseudumunasJluorescens (Suzuki, 1975).…”
Section: Discussionsupporting
confidence: 76%
“…The greatly enhanced CMcellulase activity in cellobiose-limited continuous cultures suggested that synthesis of this enzyme is catabolite repressed, as previously reported for the cellulase of R. albus (Fusee & Leatherwood, 1972) and a cellulolytic strain of PseudumunasJluorescens (Suzuki, 1975).…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies with C. thermocellum (Garcia-Martinez et al, 1980;Hammerstrom et a/., 1955) and other cellulolytic bacteria (Fusee & Leatherwood, 1972;Lee & Blackburn, 1975) demonstrated that carboxymethylcellulase is not strongly repressed by catabolism of soluble carbon sources. This was surprising since it would be advantageous for C. thermocellum to repress its level of cellulase if a soluble carbon source is available in the medium.…”
Section: Discussionmentioning
confidence: 95%
“…They appear to be similar. Results of early studies by Fusee and Leatherwood (1971) suggested that the Ruminococcus cellulase system is depressed by the presence of disaccharides such as cellobiose, sucrose, and lactose and also that cellobiose, if present, must first be used before cellulose is degraded. Inhibition of cellulose digestion by cellobiose, and to a lesser degree by glucose, was also observed by Smith et al (1973).…”
Section: 4lc Anaerobic Cellulolytic Bacteria Of Rumen and Intestinalmentioning
confidence: 99%